Tools of titans : the tactics, routines and habits of billionaires, icons and world-class performers - Ferriss, Tim, ....- (London : Ebury Publishing, 2016)
For the last two years, I've interviewed more than 200 world-class performers for my podcast, The Tim Ferriss Show. The guests range from super celebs (Jamie Foxx, Arnold Schwarzenegger, etc.) and athletes (icons of powerlifting, gymnastics, surfing, etc.) to legendary Special Operations commanders and black-market biochemists. For most of my guests, it's the first time they've agreed to a two-to-three-hour interview. This unusual depth has helped make The Tim Ferriss Show the first business/interview podcast to pass 100 million downloads.
Keywords: Business ; success